Description and DNA barcoding of Lycenchelys lenzeni, a new species of eelpout (Perciformes: Zoarcidae) from the deep sea off the Kuril Archipelago - Thiel, Ralf; Knebelsberger, Thomas; Eidus, Irina (Zootaxa, 2018)
A new species of eelpout genus Lycenchelys Gill, 1884 is described based on seven specimens caught at a depth of about 2350 m in the Bussol Strait, southwest of the Kuril Island Simushir. The species differs from its congeners in the following combination of characters: vertebrae 26–28 + 100–102 = 126–130; interorbital and occipital pores absent; postorbital pores 3–4; suborbital pores 7 (rarely 6); preoperculomandibular pores 4 + 4; gill rakers 11–16; dorsal fin rays 118–122; anal fin rays 105–108; pelvic fin rays 2; middle and lower ray tips of pectoral fin very slightly exserted; lateral line double with mediolateral and ventral branches; pyloric caeca not developed. The new species is morphologically most similar to Lycenchelys micropora and Lycenchelys jordani, which differ from the new species in having three pelvic-fin rays (vs. two pelvic-fin rays in the new species). L. micropora has the pectoral-fin origin below body midline, whereas the new species has the pectoral-fin origin at body midline. Middle and lower ray tips of pectoral fin are very slightly exserted in L. lenzeni sp. nov., whereas they are well exserted in L. jordani and L. micropora. Mitochondrial COI sequences were analyzed from four paratype specimens and all show the same haplotype sequence. The DNA barcodes allowed discrimination of L. lenzeni sp. nov. from other species of Lycenchelys where sequence data were available. The nearest match with already published sequences was Lycenchelys antarctica, with a sequence similarity of 98.25%, followed by Lycenchelys aratrirostris (sequence similarities 97.95–97.96%) and L. jordani (sequence similarity of 97.81%).